Exchange arithmetic - Holgate, H. C. F.; Syrett, W. W. (London: Pitman, 1966)
This new edition is an attempt to allow for the complications which arise from the decimalization of the pound in the United Kingdom and in Ireland. It also meets the requirements of exporting manufacturers and merchants, ship-owners among others.
Includes index
usc 26/09/18
Loans
Keywords: Foreign exchange; Business mathematics